2017
DOI: 10.1007/s13755-017-0026-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving patient engagement in self-measured blood pressure monitoring using a mobile health technology

Abstract: Objective: To understand usage patterns and clinical efficacy of Hello Heart, an mHealth technology application designed to facilitate patient engagement in managing hypertension. Methods:In this single-arm observational study, all subjects with ≥2 blood pressure (BP) recordings were included. The cohort was divided into subgroups by weeks passed since download that patients were still recording measurements. Changes in BP were compared between subgroups.Results: Of 5115 eligible subjects, 3803 (74%) recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 20 publications
(29 reference statements)
1
64
0
Order By: Relevance
“…In comparison, a study of 5115 participants that used a mHealth app to regularly measure BP, but did not give out monetary rewards, reported that 74% were using the app at 2 weeks and only 6% at 16 weeks. 25 Individuals did not receive credit for BP and PWV measurements that were outside the specified acceptable ranges, or when BP and PWV measurements were taken more than 1 hour apart. These failed ‘attempts’ were not recorded, but were filtered by the app.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, a study of 5115 participants that used a mHealth app to regularly measure BP, but did not give out monetary rewards, reported that 74% were using the app at 2 weeks and only 6% at 16 weeks. 25 Individuals did not receive credit for BP and PWV measurements that were outside the specified acceptable ranges, or when BP and PWV measurements were taken more than 1 hour apart. These failed ‘attempts’ were not recorded, but were filtered by the app.…”
Section: Resultsmentioning
confidence: 99%
“…They can also improve adherence to prescribed antihypertensive and lipid-lowering medications [ 4 ]. Lastly, HIT may alert patients and/or their care team that risk factors are less than optimal and may need intervention, such as is the case with HIT interventions that help patients and their care teams monitor blood pressure [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This paper focuses on the integration of technologies to improve the overall patient experience by reducing costs and improving quality of care. In [50], the authors explored the positive impact on the quality of care, patient satisfaction and healthcare costs by using mobile health apps such as Hello Heart which supports patient engagement in self-measured blood pressure monitoring and provides the foundation for cardiovascular diseases. Applications such as Hello Heart provide platforms to enable patients to monitor and track selfrecorded BP recordings with periodic reminders to measure BP, interactive educational modules and wireless connectivity with BP devices.…”
Section: Labelmentioning
confidence: 99%